PENINGKATKAN PEMBELAJARAN GERAK DASAR MELALUI MODEL PERMAINAN INOVATIF PADA SISWA KELAS III SD NEGERI BALAPULANG KULON 05 (Department of Physical Education, Sport, Health and Recreation, 2013)
Issues raised in this study is how to improve the learning outcomes of basic motion through an innovative gamefor the third grade students of SD Negeri 05 Balapulang Kulon?. The purpose of this study was to determinethe basic motion improvement of learning outcomes through innovative game model for third-grade students ofSD Negeri 05 Balapulang Kulon. Subjects were observed and Class III Elementary School StudentsBalapulang Kulon 05 Semester II in 2013, amounting to 22 students. Object of this study is the result oflearning the basic motion through an innovative approach to the game. The research was conducted in May of2013 that took place in the elementary school yard Balapulang Kulon 05. This study uses classroom actionresearch in the form of shaped penkajian process cycle, which consists of four stages: planning, action,observation and reflective. The research instrument using the check list to record the attitudes and events thatoccur in learning deemed important and have been set will be investigated. From the observations obtainedwith the help of a check list can be obtained that the percentage of cognitive abilities, affective and psychomotorof Elementary School Students in Grades III Balapulang Kulon 05 before the research is 68%, 64%, and 59%.After learning in cycle 1 was given an increase in cognitive ability increased to 73%, 77% affective abilities andpsychomotor skills 68%. Because there are aspects that have not reached mastery, then held a second cycle that is otherwise completed all aspects of the cognitive 86%, 91% affective, and psychomotor 86%. Conclusion isthrough learning Penjasorkes using innovative modeling approach can improve learning outcomes for studentsachieve mastery learning all aspects: cognitive, affective, and psychomotor in Class III Elementary SchoolBalapulang Kulon 05 Semester II Academic Year 2012/2013. Some suggestions include researchers, teachersshould consider the use of Penjasorkes SD innovative approach to the game because it has been proven toimprove learning outcomes of students achieve mastery learning in learning basic movement. In the applicationof learning Penjasorkes using innovative approaches in order to achieve the game that teachers need to planoptimal learning scenarios that put more on the active involvement and fun of all students in learning activities.